Nivel de cocimientos y practicas de las enfermeras sobre aspiración de secreciones en pacientes intubados en la unidad de cuidados intensivos y emergencias - Pilcón Gonzales, Karina (2017)
The present study is a correlational descriptive, which was to determine the level of knowledge and practices of nurses on aspiration of secretions in patients intubated in the Intensive Care Unit and Emergencies of Hospital Belén de Trujillo; The sample consisted of 32 nurses, respectively. The instrument conformed by the questionnaire and the checklist, applied prior informed consent. It is concluded that of the total 100%; 25% have good knowledge and 75% have poor knowledge; While 59.4% nurses have adequate practices and 40.6% have inadequate secretion aspiration practices. For data processing, one- and double-entry frequency distribution tables were used, with their absolute and relative values. To determine the relationship between the level of knowledge and the level of practice, the non-parametric criterion independence test was used using the chi-square distribution (X2) or Fisher's exact test, concluding that the level of knowledge of nurses significantly influences (P = 0.00069), in the aspiration practices of secretions in the intubated patient.